Short-term mortality of patients ≥80 years old admitted to European intensive care units: an international observational study. (July 2022) - Fronczek, Jakub; Flaatten, Hans; Guidet, Bertrand; Polok, Kamil; Andersen, Finn H.; Andrew, Benjamin Y.; Artigas, Antonio; Beil, Michael; Cecconi, Maurizio; Christensen, Steffen; de Lange, Dylan W.; Fjølner, Jesper; et al.
Abstract: Background: Limited evidence suggests variation in mortality of older critically ill adults across Europe. We aimed to investigate regional differences in mortality among very old ICU patients. Methods: Multilevel analysis of two international prospective cohort studies. We included patients ≥80 yr old from 322 ICUs located in 16 European countries. The primary outcome was mortality within 30 days from admission to the ICU. Results are presented as n (%) with 95% confidence intervals and odds ratios (ORs). Results: Of 8457 patients, 2944 (36.9% [35.9–38.0%]) died within 30 days. Crude mortality rates varied widely between participating countries (from 10.1% [6.4–15.6%] to 45.1% [41.1–49.2%] in the ICU and from 21.3% [16.3–28.9%] to 55.3% [51.1–59.5%] within 30 days). After adjustment for confounding variables, the variation in 30-day mortality between countries was substantially smaller than between ICUs (median OR 1.14 vs 1.58). Healthcare expenditure per capita (OR=0.84 per $1000 [0.75–0.94]) and social health insurance framework (OR=1.43 [1.01–2.01]) were associated with ICU mortality, but the direction and magnitude of these relationships was uncertain in 30-day follow-up. Volume of admissions was associated with lower mortality both in the ICU (OR=0.81 per 1000 annual ICU admissions [0.71–0.94]) and in 30-day follow-up (OR=0.86 [0.76–0.97]). Conclusion: The apparent variation in short-term mortality rates of older adults hospitalised in ICUs across Europe can be largely attributed to differences in the clinical profile of patients admitted. The volume–outcome relationship identified in this population requires further investigation.